Revisiting the engineering mathematics curriculum offered to engineering undergraduates - Maz Jamilah, Masnan; Abdull Halim, Abdul; Aishah, Mohd Noor (Universiti Teknologi Malaysia (UTM), 2008)
Organized by Universiti Teknologi Malaysia (UTM), 3rd - 5th December 2007 at Persada Johor International Convention Centre, Johor Bahru.